Apoptosis via cytochrome c in aortic tissue of diabetes mellitus after giving sikkam leaves (Bischofia javanica Blume) - Syafruddin Ilyas; Salomo Hutahaean; Rahmat SH. Sinaga; Putri C. Situmorang (GarVal Editorial Ltda., 2021)
Context: Diabetes mellitus (DM) is a metabolic hyperglycemia disease caused by abnormalities in insulin secretion and the highest increase in diabetes sufferers that occurred in Southeast Asian countries, including Indonesia. The sikkam leaf (Bischofia javanica) ethanolic extract contains many secondary metabolites, and some of them are quercetin and gallic acid, which have the potential to be used as antidiabetic. Aims: To analyze apoptosis via cytochrome c in aortic tissue of DM after giving B. javanica leaves. Methods: The treatment group consisted of G0: Negative control, G1: Positive control (alloxan induction + standard feed), G2: Alloxan induction + 300 mg/kg BW of B. javanica leaves ethanol extract, G3: Alloxan induction + 600 mg/kg BW of B. javanica leaves ethanol extract, G4: Induction of alloxan + ethanol extract of B. javanica leaves 900 mg/kg BW and G5: Induction of alloxan + glibenclamide 0.5 mg/kg BW. Fourteen days later, the rats were dissected, and the aortic tissue was analyzed for apoptosis by tunnel assay and cytochrome c by immunohistochemistry. Results: There was a statistically significant difference (p<0.01) in the apoptotic value and cytochrome c. Increasing the dose of B. javanica leaves, the cytochrome c expression, and apoptotic value decreases in the aorta of DM rats. The cell shape returned to normal after being given B. javanica ethanol extract 900 mg/kg BW than glibenclamide. Conclusions: Bischofia javanica ethanolic extract reduced apoptosis via cytochrome c in aortic histology, and this plant can be developed into a diabetic drug candidate.